2019
DOI: 10.1007/s11145-019-09950-x
|View full text |Cite
|
Sign up to set email alerts
|

Argumentative writing: theory, assessment, and instruction

Abstract: Despite the early emergence of oral argumentation, written argumentation is slow to develop, insensitive to alternative perspectives, and generally of poor quality. These findings are unsettling because high quality argumentative writing is expected throughout the curriculum and needed in an increasingly competitive workplace that requires advanced communication skills. In this introduction, we provide background about the theoretical perspectives that inform the papers included in this special issue and highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 62 publications
1
52
0
2
Order By: Relevance
“…A review of related research reveals the effectiveness of process approach to writing on learners' writing achievement in general (Allen et al, 2019;Ferretti & Graham, 2019). By comparing process and product approaches to writing instruction, Tong (2007) concluded that the process approach was more effective in developing the writing proficiency of the learners.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A review of related research reveals the effectiveness of process approach to writing on learners' writing achievement in general (Allen et al, 2019;Ferretti & Graham, 2019). By comparing process and product approaches to writing instruction, Tong (2007) concluded that the process approach was more effective in developing the writing proficiency of the learners.…”
Section: Review Of Literaturementioning
confidence: 99%
“…As an argumentative text has its own complexity, researchers or educators measure students' writing performances in relatively isolated contexts, such as a rhetorical difficulty for second and foreign language writers (Zhu, 2001), an assessment of writing performance (Allen, Likens, & McNamara, 2019), and writing quality (Kim, Gatlin, Otaiba, & Wanzek, 2018). Additionally, some studies have commonly revolved around the assessment and the analysis of the linguistic and rhetorical features of argumentative essays (Ferretti & Graham, 2019;MacArthur, Jennings, & Philippakos, 2019). In most writing research, participants were asked to write essays in response to a single prompt or more prompts.…”
Section: Linguistics Features To Analyze Argumentative Textsmentioning
confidence: 99%
“…We draw primarily on a sociocultural perspective for understanding argument. In this view, arguments are seen as social acts where the interchange between people shapes ideas (Bazerman, 2015; Ferretti & Graham, 2019). In their discussion of argument, Ferretti and Lewis (2018) assert that “argumentation is an inherently social activity involving dialogue among people who may hold different perspectives about a controversial issue” (p. 137).…”
Section: Perspectivesmentioning
confidence: 99%